2x+6+3x-4=37

Simple and best practice solution for 2x+6+3x-4=37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6+3x-4=37 equation:


Simplifying
2x + 6 + 3x + -4 = 37

Reorder the terms:
6 + -4 + 2x + 3x = 37

Combine like terms: 6 + -4 = 2
2 + 2x + 3x = 37

Combine like terms: 2x + 3x = 5x
2 + 5x = 37

Solving
2 + 5x = 37

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 5x = 37 + -2

Combine like terms: 2 + -2 = 0
0 + 5x = 37 + -2
5x = 37 + -2

Combine like terms: 37 + -2 = 35
5x = 35

Divide each side by '5'.
x = 7

Simplifying
x = 7

See similar equations:

| e^2x=2.4 | | 3.50x+1.50=21 | | 20x-9=12x+89 | | 3*x+4*y=73*x+4*y=7 | | x*-5x+4=0 | | X^2+2xr+r^2=0 | | -9x-3=-9+5 | | 5c+12-3c=12 | | 4-2x=y | | 2(x-9)=12-(x+2) | | 3.2m-4-3.2m-6= | | 21x+1=18x+3 | | 8x^6+125=0 | | (x-3)(2x)=1.25x | | (1-v)(2v+9)=0 | | 8=-10-3y | | x+x+5=-55 | | 14x-60=38 | | -0.02857142857x^2+0.45714285714x+1.02857142857=y | | -2(3x-2)+x+9whenx=3 | | X(x)-8x+c=0 | | 10=3(x-1)-(x-5) | | 9x-3=8-7x | | 3(2x-5)-3=3(x-2)+9 | | x*x+2*5=236 | | x^2+28x+52=0 | | 4x-(5x+5)=3x-45 | | x+x+x+x+x+5-18+90=180 | | 3x+3iy-2ix-2y=4+i | | (a+5-b)(a-13+2b)=0 | | 5(x-6)=11-(x+1) | | 5x+18+90=180 |

Equations solver categories